A linguistic guide to English poetry - Geoffrey N Leech (London- Harlow Longmans, 1969)
"Professor Leech has given us the first full-length textbook suitable for teaching the 'new stylistics' to undergraduates."Language and Style
Keywords: English poetry -- History and criticism; Poetics; English language -- Style